Clinical, Aesthetic, and Patient‐Related Outcome of Immediately Loaded Single Implants in the Anterior Maxilla: A Prospective Study in Extraction Sockets, Healed Ridges, and Grafted Sites. (17th January 2012) - Raes, Filiep; Cosyn, Jan; De Bruyn, Hugo
ABSTRACT Purpose: The objective of this prospective clinical study was to document the overall treatment outcome of immediately loaded single Astra Tech Osseospeed™ (Astra Tech AB, Mölndal, Sweden) implants placed in extraction sockets, healed ridges, and grafted sites. Materials and Methods: Forty‐eight patients in need of a single implant in the anterior maxilla (15–25) were recruited. Patients were allocated to a conventional implant treatment (CIT) or immediate implant treatment (IIT) group on the basis of specific criteria. If the buccal bone plate was damaged or missing upon tooth removal, patients were allocated to a grafted implant treatment (GIT) group. Irrespective of the treatment concept, implants were immediately provisionalized. Hard and soft tissue alterations, aesthetic parameters (pink and white esthetic scores, [PES and WES]) and patient's opinion (Oral Health Impact Profile [OHIP‐14] questionnaires) were registered at different time points. Results: After 1 year of function, the overall implant survival rate was 98% with one failure following IIT. The mean bone level to the implant‐abutment interface was 0.65 (SD 0.79), 0.85 (SD 0.64), and 0.56 mm (SD 0.44) for CIT, IIT, and GIT. Complete papilla loss was rare following either strategy. Mean midfacial recession amounted to 1.00 (SD 1.15), 0.12 (SD 0.78), and 0.49 mm (SD 0.82) for CIT, IIT, and GIT, respectively. The aesthetic outcome showed a mean PES of 10.30 (SD 1.89) and mean WES of 7.11 (SD 2.14), all patients considered. Patient's satisfaction showed a significant improvement after 1 year of function on all seven domains (p < .001). Conclusions: This prospective study showed that single implants clinically and aesthetically perform well under immediate non‐occlusal loading conditions in the premaxilla. In this context, it is of pivotal importance to stress that patients were carefully selected for IIT and GIT.